2024
DOI: 10.3390/make6010016
|View full text |Cite
|
Sign up to set email alerts
|

SHapley Additive exPlanations (SHAP) for Efficient Feature Selection in Rolling Bearing Fault Diagnosis

Mailson Ribeiro Santos,
Affonso Guedes,
Ignacio Sanchez-Gendriz

Abstract: This study introduces an efficient methodology for addressing fault detection, classification, and severity estimation in rolling element bearings. The methodology is structured into three sequential phases, each dedicated to generating distinct machine-learning-based models for the tasks of fault detection, classification, and severity estimation. To enhance the effectiveness of fault diagnosis, information acquired in one phase is leveraged in the subsequent phase. Additionally, in the pursuit of attaining m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The SHAP summary plot in the present study identified activity, rest time, and rest per bout as the most crucial features for developing an effective calving day prediction model. The SHAP summary plot illustrates each dot as a single SHAP value for a specific feature within a single data instance [ 42 ]. Notably, the clustering of dots reflects the strength of a feature’s interaction with the model’s outcomes [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SHAP summary plot in the present study identified activity, rest time, and rest per bout as the most crucial features for developing an effective calving day prediction model. The SHAP summary plot illustrates each dot as a single SHAP value for a specific feature within a single data instance [ 42 ]. Notably, the clustering of dots reflects the strength of a feature’s interaction with the model’s outcomes [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The SHAP summary plot in the present study identified Using a Shapley Additive Explanation (SHAP) model, the present study evaluated the importance of features for calving day predictions in ML models. This model leverages concepts from game theory [42] and integrates seamlessly with the random forest regressor model in the present study [43] to illustrate the contribution of each input variable to the prediction of calving day models. Figure 10 presents the mean absolute SHAP values for each feature.…”
Section: Machine Learning Model Evaluationmentioning
confidence: 99%
“…These models learn the relationships between different material properties (independent variables) and compressive strength (dependent variable), allowing researchers to identify the most signi cant factors in uencing strength. Also, techniques like SHAP (SHapley Additive exPlanations) values within machine learning models pinpoint which speci c features within the material data contribute most signi cantly to the predicted strength [22].…”
Section: Introductionmentioning
confidence: 99%